CONSUMER DECISION MODEL (CDM) ANALYSIS OF EFFECTIVENESS VIDEOTRON ADVERTISING SERVED IN SURAKARTA - Muhammad Khoiruman; Ambar Warniati (ProBank, 2017)
This study aims to analyze the effectiveness of Videotron media ads served in Surakarta using the Consumer Decision Model (CDM) Analysis. Viewed ad serving costs in videtron large enough it is necessary to study the effectiveness of the ads served on videtron. The model that is used in measuring the effectiveness of an ad in this research is the Consumer Decision Model (CDM). The research objective was to determine the effect the message of the ad (Information), branding (Brand Recognition), the formation of an attitude (Attitude), the level of confidence in the message (Confidence), and intention to purchase (Intention) market target after seeing ad impressions through Videotron. The study population is a society in Surakarta with sampling method is purposive sampling of 200 respondents Data analysis technique using Structural Equation Modeling (SEM) which resulted in the conclusion that the message of the ad (Information) positive effect but not significant with branding (Brand Recognition), formation attitude (attitude), and the level of confidence in the message (confidence). Brand recognition is positive and significant impact on the confidence and attitude while confidence and attitude positive and significant effect on the intention to purchase (Intention) market target after seeing ad impressions through Videotron. Outcomes of this study are: enrichment of teaching materials, especially marketing management, Scientific publications (national journals) and an input for an advertiser, the advertising company and the Government of Surakarta about the effectiveness of the ads served through Videotron so they can be a policy in the future.Keywords: Videotron, advertising, Consumer Decision Model, Information, Brand Recognition, Attitude, Confidence, and Intention